Different drummers: military culture and its discontents - Tuleja, Tad, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2020)
Explores the disjunction between organizational solidarity and individual pushback in military organizations, examining how members of the armed forces express ambivalent or conflicted attitudes about their service. The volume focuses on psychological "discontent" within loyal opposition, considering examples of creative insubordination and analyzing 'oppositional positioning'.--Provided by publisher.
Introduction: the myth of the robot soldier / Tad Tuleja -- On the griping of grunts / Angus Kress Gillespie -- Back chat: subversion and conformity in Dominion cartoons of the world wars / Christina M. Knopf -- Warriors' bodies as sites of microresistance in the American military / John Paul Wallis & Jay Mechling -- Jumping the chain: a military psychologist's story / Mark C. Russell -- A captain's first duty: managing command disconnect in a combat zone / Ronald Fry -- (De)composing the "Machine of Decomposition": creative insubordination in E.E. Cummings's The Enormous Room / Matthew David Perry -- Café colonels and whizz bangs / Tad Tuleja -- The wild deserters of no man's land: a ghoulish legend of the Great War / James I. Deutsch -- Breaking ranks: initiative and heroism in a Vietnam firefight / Richard Allen Burns -- Challenging the male hierarchy: women warriors in Iraq and Afghanistan / Catherine Calloway -- So I was a coffin: the war poetry of Gerardo Mena / Ron Ben-Tovim -- Telling stories in war / Carol Burke -- Discipline and the limits of unit cohesion / Tad Tuleja.
Keywords: Insubordination; Soldiers -- Attitudes; Soldiers -- Conduct of life; Military discipline; Armed Forces -- Regulations